PENGARUH PEMBELAJARAN MENGGUNAKAN MEDIA QUIPPER SCHOOL TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON-ELEKTROLIT - Sulfi Asmaputri; fitri refelita (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
This research was instigated by the low of student learning achievement, student learning interest, and the use of internet based instructional media at the school.  It was based on the results of preliminary observation that was conducted in the Chemistry learning process.  The use of Quipper School instructional media aimed at increasing student learning interest in order to increase student learning achievement.  This research aimed at knowing whether there was an effect of learning using Quipper School media toward student learning achievement and interest on Electrolyte and Non-Electrolyte Solution lesson.  It was an experimental research.  All the tenth-grade students of Senior High School of Muhammadiyah 1 Pekanbaru, there were 6 classes and 166 students.  Purposive sampling technique was used in this research.  In this case, the tenth-grade students of Natural Science 3 were selected as the samples based on the observation in the field and Chemistry subject teacher consideration at the school.  There were two instruments, student learning interest questionnaire and learning achievement test question.  Techniques of processing and analyzing the data were descriptive and inferential statistics.  The results of hypothesis testing in this research showed that there was an effect of using quipper school media toward student learning achievement and interest, tobserved ≥ ttable (2.064>9.820) and there was an effect of using Quipper School media toward student learning achievement. The score was tobserved≥ttable (2.064>9.820),   So, H0 was rejected and Ha was accepted.  Based on the research findings, it could be concluded that  there was an effect of learning using Quipper School media  toward student learning achievement and interest on Electrolyte and Non-Electrolyte Solution lesson.Keywords:     Learning Achievement, Learning Interest,  Quipper School, Electrolyte and Non-Electrolyte Solution